MYCOTOXICOLOGICAL AND PHYSICOCHEMICAL STUDY OF INFANT FLOUR MYCOTOXICOLOGICAL AND PHYSICOCHEMICAL STUDY OF INFANT FLOUR MYCOTOXICOLOGICAL AND PHYSICOCHEMICAL STUDY OF INFANT FLOUR MYCOTOXICOLOGICAL AND PHYSICOCHEMICAL STUDY OF INFANT FLOUR MYCOTOXICOLOGICAL AND PHYSICOCHEMICAL STUDY OF INFANT FLOUR MYCOTOXICOLOGICAL AND PHYSICOCHEMICAL STUDY OF INFANT FLOUR MYCOTOXICOLOGICAL AND PHYSICOCHEMICAL STUDY OF INFANT FLOUR MYCOTOXICOLOGICAL AND PHYSICOCHEMICAL STUDY OF INFANT FLOUR MYCOTOXICOLOGICAL AND PHYSICOCHEMICAL STUDY OF INFANT FLOUR MYCOTOXICOLOGICAL AND PHYSICOCHEMICAL STUDY OF INFANT FLOUR MYCOTOXICOLOGICAL AND PHYSICOCHEMICAL STUDY OF INFANT FLOUR MYCOTOXICOLOGICAL AND PHYSICOCHEMICAL STUDY OF INFANT FLOUR MYCOTOXICOLOGICAL AND PHYSICOCHEMICAL STUDY OF INFANT FLOUR MYCOTOXICOLOGICAL AND PHYSICOCHEMICAL STUDY OF INFANT FLOUR MYCOTOXICOLOGICAL AND PHYSICOCHEMICAL STUDY OF INFANT FLOUR MYCOTOXICOLOGICAL AND PHYSICOCHEMICAL STUDY OF INFANT FLOUR MYCOTOXICOLOGICAL AND PHYSICOCHEMICAL STUDY OF INFANT FLOUR MYCOTOXICOLOGICAL AND PHYSICOCHEMICAL STUDY OF INFANT FLOUR MYCOTOXICOLOGICAL AND PHYSICOCHEMICAL STUDY OF INFANT FLOUR MYCOTOXICOLOGICAL AND PHYSICOCHEMICAL STUDY OF INFANT FLOUR MYCOTOXICOLOGICAL - A, . Khaldi*1; A., Moussaoui1; B., Meddah1,2 (university of eloued جامعة الوادي, 2020)
The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of The current work focuses on a mycotoxicological study and the control of physicochemical quality of infantile flours marketed in the city Becha physicochemical quality of infantile flours marketed in the city Bechaphysicochemical quality of infantile flours marketed in the city Becha physicochemical quality of infantile flours marketed in the city Becha physicochemical quality of infantile flours marketed in the city Becha physicochemical quality of infantile flours marketed in the city Bechaphysicochemical quality of infantile flours marketed in the city Bechaphysicochemical quality of infantile flours marketed in the city Becha physicochemical quality of infantile flours marketed in the city Becha physicochemical quality of infantile flours marketed in the city Becha physicochemical quality of infantile flours marketed in the city Becha physicochemical quality of infantile flours marketed in the city Becha physicochemical quality of infantile flours marketed in the city Becha physicochemical quality of infantile flours marketed in the city Becha physicochemical quality of infantile flours marketed in the city Becha physicochemical quality of infantile flours marketed in the city Becha physicochemical quality of infantile flours marketed in the city Becha physicochemical quality of infantile flours marketed in the city Becha physicochemical quality of infantile flours marketed in the city Becha physicochemical quality of infantile flours marketed in the city Becha physicochemical quality of infantile flours marketed in the city Becha physicochemical quality of infantile flours marketed in the city Becha physicochemical quality of infantile flours marketed in the city Bechaphysicochemical quality of infantile flours marketed in the city Becha physicochemical quality of infantile flours marketed in the city Becha physicochemical quality of infantile flours marketed in the city Becha physicochemical quality of infantile flours marketed in the city Bechaphysicochemical quality of infantile flours marketed in the city Bechaphysicochemical quality of infantile flours marketed in the city Bechaphysicochemical quality of infantile flours marketed in the city Becha r in thr in thr in th r in th e Southe Southe Southe South -West West West of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the of Algeria, thus aiming to study phenolic composition, antioxidant activity and efficacy the antianti -mycotoxin effect of the aqueous extract mycotoxin effect of the aqueous extract mycotoxin effect of the aqueous extract mycotoxin effect of the aqueous extract mycotoxin effect of the aqueous extract mycotoxin effect of the aqueous extract mycotoxin effect of the aqueous extract mycotoxin effect of the aqueous extract mycotoxin effect of the aqueous extract mycotoxin effect of the aqueous extract mycotoxin effect of the aqueous extract mycotoxin effect of the aqueous extract mycotoxin effect of the aqueous extract Anethum graveolens Anethum graveolensAnethum graveolens Anethum graveolensAnethum graveolens L. The The The mycotoxicological mycotoxicological analysisanalysis analysis analysis revealed revealed revealedrevealedrevealedrevealed that the that the first first sample of the inf sample of the inf sample of the infsample of the infsample of the inf sample of the inf sample of the inf ant floant flo ant flo ur type I (FIT I/E1) is unsatisfactory ur type I (FIT I/E1) is unsatisfactory ur type I (FIT I/E1) is unsatisfactory ur type I (FIT I/E1) is unsatisfactory ur type I (FIT I/E1) is unsatisfactory ur type I (FIT I/E1) is unsatisfactory ur type I (FIT I/E1) is unsatisfactory ur type I (FIT I/E1) is unsatisfactory ur type I (FIT I/E1) is unsatisfactory ur type I (FIT I/E1) is unsatisfactory ur type I (FIT I/E1) is unsatisfactory ur type I (FIT I/E1) is unsatisfactory ur type I (FIT I/E1) is unsatisfactory ur type I (FIT I/E1) is unsatisfactory ur type I (FIT I/E1) is unsatisfactory product with a contamination rate 12.54 × 10 product with a contamination rate 12.54 × 10product with a contamination rate 12.54 × 10 product with a contamination rate 12.54 × 10 product with a contamination rate 12.54 × 10product with a contamination rate 12.54 × 10product with a contamination rate 12.54 × 10product with a contamination rate 12.54 × 10 product with a contamination rate 12.54 × 10product with a contamination rate 12.54 × 10 product with a contamination rate 12.54 × 10 product with a contamination rate 12.54 × 10 product with a contamination rate 12.54 × 10 product with a contamination rate 12.54 × 10 product with a contamination rate 12.54 × 10 product with a contamination rate 12.54 × 10 product with a contamination rate 12.54 × 10product with a contamination rate 12.54 × 10product with a contamination rate 12.54 × 10 3 UF/g UF/g whose 40% of 40% of 40% of 40% of Aspergillus flavus Aspergillus flavusAspergillus flavus Aspergillus flavus Aspergillus flavus Aspergillus flavus Aspergillus flavus strains strains isolated isolatedisolated are producers ofare producers ofare producers ofare producers ofare producers of are producers ofare producers ofare producers of are producers of aflatoxin B1aflatoxin B1 aflatoxin B1 aflatoxin B1 aflatoxin B1aflatoxin B1 and 50% of and 50% of and 50% of and 50% of and 50% of and 50% of A ochraceusA ochraceusA ochraceus A ochraceus A ochraceusA ochraceus are producers ofare producers of are producers ofare producers of are producers ofare producers ofare producers of are producers of ochratoxin ochratoxin ochratoxinochratoxin ochratoxin A. The aqueous extract of The aqueous extract of The aqueous extract of The aqueous extract of The aqueous extract of The aqueous extract of The aqueous extract of The aqueous extract of The aqueous extract of The aqueous extract of The aqueous extract of The aqueous extract of A gA gA graveole raveoleraveole raveolens L. showed significant anti L. showed significant antiL. showed significant anti L. showed significant antiL. showed significant antiL. showed significant anti L. showed significant anti L. showed significant antiL. showed significant anti L. showed significant antiL. showed significant anti -mycotoxin activity, mycotoxin activity, mycotoxin activity, mycotoxin activity, mycotoxin activity, mycotoxin activity, mycotoxin activity, A flavusA flavusA flavus A flavus A flavusA flavus was i was i nhibited from a nhibited from a nhibited from a nhibited from a minimum inhibitory concentration minimum inhibitory concentration minimum inhibitory concentration minimum inhibitory concentration minimum inhibitory concentration minimum inhibitory concentration minimum inhibitory concentrationminimum inhibitory concentration minimum inhibitory concentrationminimum inhibitory concentration minimum inhibitory concentration MIC of 300 μg/ml and MIC of 300 μg/ml and MIC of 300 μg/ml and MIC of 300 μg/ml and MIC of 300 μg/ml and MIC of 300 μg/ml and MIC of 300 μg/ml and A ochraceusA ochraceus A ochraceus A ochraceusA ochraceus at at at 650 μg/ml. 650 μg/ml. 650 μg/ml. 650 μg/ml. 650 μg/ml. The total phenol content The total phenol content The total phenol content The total phenol content The total phenol content The total phenol content The total phenol content The total phenol content The total phenol content The total phenol content The total phenol content is also determined for extract. The antioxidant activitie also determined for extract. The antioxidant activitie also determined for extract. The antioxidant activitie also determined for extract. The antioxidant activitie also determined for extract. The antioxidant activitie also determined for extract. The antioxidant activitie also determined for extract. The antioxidant activitie also determined for extract. The antioxidant activitie also determined for extract. The antioxidant activitie also determined for extract. The antioxidant activitie also determined for extract. The antioxidant activitie also determined for extract. The antioxidant activitie also determined for extract. The antioxidant activitie also determined for extract. The antioxidant activitie also determined for extract. The antioxidant activitie also determined for extract. The antioxidant activitie also determined for extract. The antioxidant activitie also determined for extract. The antioxidant activitie also determined for extract. The antioxidant activitie also determined for extract. The antioxidant activitie also determined for extract. The antioxidant activitie also determined for extract. The antioxidant activitie was estimated was estimated was estimated was estimated was estimated was estimated and tand t and the aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with he aqueous extract showed a good scavenging activity with a concentration providing 50% inhibition concentration providing 50% inhibition concentration providing 50% inhibition concentration providing 50% inhibition concentration providing 50% inhibition concentration providing 50% inhibition concentration providing 50% inhibition concentration providing 50% inhibition concentration providing 50% inhibition concentration providing 50% inhibition concentration providing 50% inhibition concentration providing 50% inhibition (IC 50 ) value value of 0,14±0,31 mg/ml 0,14±0,31 mg/ml 0,14±0,31 mg/ml.
artical
Keywords: Infant flourInfant flour Infant flourInfant flour ; mycotoxins ; Anethum graveolens Anethum graveolens Anethum graveolensAnethum graveolens L. ; antianti -mycotoxin activity mycotoxin activity mycotoxin activity mycotoxin activity mycotoxin activity.